BAGAIMANA WARGA BINAAN DENGAN KASUS PENCABULAN ANAK MEMAKNAI VONISNYA? INTERPRETATIVE PHENOMENOLOGICAL ANALYSIS - Kaloeti, Dian Veronika Sakti; La Kahija, Yohanis Franz; Salma, Salma (Jurnal Psikologi, 2019)
Child molestation was a form of child exploitation which gets serious concern from Indonesian government. A number of literatures has been investigated on traumatic effect of child predatory among children. However, study which explored child molester’s lived experience was still limited. This study aims to understand the lived experience of child molester after being sentenced. Three prisoners of Correctional Institution Kedungpane Semarang Indonesia were interviewed using semi-structured interview. Using interpretative phenomenological analysis, data were analyzed. Four superordinate themes emerged from analysis: (1) failure to resolve conflicts with victim’s family, (2) disappointment of case disclosure, (3) attempt to escape severe punishment, and (4) effort to accept sentence. This result showed the need to find more effective strategy to help prisoners understand the effect of their behavior to children. Some suggestions to improve insight process among child molesters were also proposed.